Biomolecular Triconjugates Formed between Gold, Protamine, and Nucleic Acid: Comparative Characterization on the Nanoscale - Robert K. DeLong; Lisa Cillessen; Chris Reynolds; Adam Wanekaya; Tiffany Severs; Kartik Ghosh; Michael Fisher; Stephanie Barber; John Black; Ashley Schaeffer; Kristin J. Flores (Journal of Nanotechnology)
DNA and RNA micro- and nanoparticles are increasingly being used for gene and siRNA drug delivery and a variety of other applications in bionanotechnology. On the nanoscale, these entities represent unique challenges from a physicochemical characterization perspective. Here, nucleic acid conjugates with protamine and gold nanoparticles (GNP) were characterized comparatively in the nanorange of concentration by UV/Vis NanoDrop spectroscopy, fluorimetry, and gel electrophoresis. Given the intense interest in splice-site switching oligomers (SSOs), we utilized a human tumor cell culture system (HeLa pLuc-705), in which SSO-directed splicing repair upregulates luciferase expression, in order to investigate bioactivity of the bionanoconjugates. Process parameters important for bioactivity were investigated, and the bimolecular nanoconjugates were confirmed by shifts in the dynamic laser light scatter (DLLS), UV/Vis spectrum, gel electrophoresis, or sedimentation pattern. The data presented herein may be useful in the future development of pharmaceutical and biotechnology formulations, processes, and analyses concerning protein, DNA, or RNA bionanoconjugates.